Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s12275-016-6029-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural insight for substrate tolerance to 2-deoxyribose-5-phosphate aldolase from the pathogen Streptococcus suis

Abstract: 2-deoxyribose-5-phosphate aldolase (DERA) is a class I aldolase that catalyzes aldol condensation of two aldehydes in the active site, which is particularly germane in drug manufacture. Structural and biochemical studies have shown that the active site of DERA is typically loosely packed and displays broader substrate specificity despite sharing conserved folding architecture with other aldolases. The most distinctive structural feature of DERA compared to other aldolases is short and flexible C-terminal regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In all the available crystal structures of DERAs containing a C-terminal tyrosine, 24 , 32 , 33 , 35 , 36 , 74 the electron density for the C-terminal tail is poorly defined, which prevents understanding the structural and functional basis of the participation of Y259 in catalysis. To characterize the dynamics of the C-terminal tail in solution, we acquired { 1 H} 15 N heteronuclear NOE (hetNOE) values for DERAm.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In all the available crystal structures of DERAs containing a C-terminal tyrosine, 24 , 32 , 33 , 35 , 36 , 74 the electron density for the C-terminal tail is poorly defined, which prevents understanding the structural and functional basis of the participation of Y259 in catalysis. To characterize the dynamics of the C-terminal tail in solution, we acquired { 1 H} 15 N heteronuclear NOE (hetNOE) values for DERAm.…”
Section: Resultsmentioning
confidence: 99%
“… 23 Therefore, DERA is considered as a promising pharmaceutical target against human bacterial pathogens. 24 , 25 In addition to this, DERA is unique in catalyzing the cross-aldol condensation between two aldehydes and is utilized as an environmentally friendly biocatalyst for the synthesis of drugs such as statins. 26 28 However, the absence of a phosphate group from the substrate severely curtails the catalytic efficiency of DERA, 29 thereby restricting its use as an efficient biocatalyst to phosphorylated aldehydes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural studies have shown that the wide substrate tolerance range of DERA is related to the C-terminus which is shorter and more flexible than that of other classes of aldolases. [32] This C-terminal tail generates an equilibrium between an open and a closed state. In the closed state, the C-terminal tyrosine enters to the active site to participate in a catalytic deprotonation step, while the open state allows substrate binding and product release.…”
Section: Chembiochemmentioning
confidence: 99%